Plasma-activated water accelerates wound healing and reduces Staphylococcus aureus infection in vivo - Adrian I. Abdo; Hang T. Nguyen; Laurine D. Kaul; Thomas Schmitt-John; Zlatko Kopecki; Abiodun D. Ogunniyi; Katharina Richter (Biofilm)
Chronic wound infections are notoriously difficult to treat due to bacterial biofilms – protective communities of microbes that can resist antibiotics and host defenses. With rising antimicrobial resistance, there is an urgent need for non-antibiotic therapies that can effectively disrupt biofilms and promote wound healing. Plasma-activated water (PAW), produced by bubbling cold plasma into water, creates an antimicrobial solution rich in reactive oxygen and nitrogen species. In this study, we investigated the efficacy of PAW as a topical wound cleanser. In vitro, we demonstrated that PAW effectively eradicated biofilm-forming bacteria, including Staphylococcus spp., Acinetobacter baumannii and Escherichia coli, achieving a reduction of 2.99–4.41 log10(colony forming units [CFU]/mL). In vivo, PAW significantly improved Galleria mellonella larvae survival from infection with methicillin-resistant Staphylococcus aureus (MRSA) or Staphylococcus epidermidis. Moreover, we treated scald burn wounds infected with bioluminescent MRSA biofilm in BALB/c mice with twice-daily topical PAW application. Compared to vehicle, PAW significantly reduced bacterial load from day 4–7 (0.44–0.49 log10[photons/s] reduction, p ≤ 0.0337), with endpoint analysis confirming a 1.33 log10[CFU/g] reduction (p = 0.0032). Histological assessment showed significantly improved wound re-epithelialisation in PAW-treated mice (63.2 %) compared to vehicle (49.2 %, p = 0.0093). These results demonstrate that PAW is a safe, effective antimicrobial wound cleanser with biofilm-disrupting and tissue-healing properties. Based on these findings, a clinical phase I trial is planned to evaluate PAW as an adjuvant to standard wound care in the treatment of diabetic foot wounds.